Genetic characterization of maize for stenocarpella maydis ear rot resistance - Moremoholo, Lieketso (My University, 2008)
Stenocarpella ear rot caused by Stenocarpella maydis (Berck) Sutton is the most important disease of maize in South Africa. It is a sporadic disease which makes it difficult for farmers to prepare for its occurrence and consequently of the control measure. The objectives of this study were to genetically characterise the resistance of Stenocarpella maydis ear rot and to identify agronomically suitable Stenocarpella ear rot resistant inbred lines with good combining ability for grain yield. The experimental design was a randomised complete block design with three replications. Studies were conducted at Bethlehem, Cedara and Potchefstroom. To facilitate the comparison, separate trials were established for inbred lines and top cross hybrids. Fifty-four inbred lines were compared against four inbred lines vs. E739, DO620Y, H111 and Mo17 that are well adapted and stable yielders possessing variable resistance to Stenocarpella maydis ear rot. Fifty-four top crosses were compared against one open pollinated variety (SAM 1066), which was used as a tester line as well as three commercial hybrids vs. PAN 6124BT, PAN 6026 and CRN 3505. At Potchefstroom there was an inoculation trial using both inbreds and top crosses. The inbred and top cross materials were obtained from 2004/05 breeding nursery under natural infestation of Stenocarpella maydis at Agricultural Research Council-Grain Crops Institute, Potchefstroom. Data collected were number of days to 50% silking, plant and ear height in centimetres, husk cover, ear position, stand count, total number of ears, number of diseased ears and lodging resistance,. Entries 43 and 4 were the most stable inbred lines with a beta close to 1, while entries 9 and 25 had the smallest deviation from regression. Among the tested inbred lines entry 47 was superior over other inbred lines for grain yield followed by entry 4. Entry 47 showed grain yield of 2.84 tons ha-1 at Bethlehem and 4.42 tons ha-1 at Potchefstroom. While entry 4 had a grain yield of 2.19 tons ha-1 at Bethlehem and 4.58 tons ha-1at Potchefstroom. The two lines, however, are poor combiners for both grain yield and Stenocarpella maydis ear rot resistance. Using SAM 1066 as a tester the grain yield observed for top crosses at Bethlehem, Cedara and Potchefstroom were 5.94, 7,15 and 9.95 tons ha-1, respectively. Entries 57 and 14 were the most stable top cross hybrids with a beta close to one, while entries 46 and 47 had the smallest deviation from regression. Entries 56 and 28 were the most superior top cross hybrids. Entry 56 showed grain yield of 5.58 tons ha-1 at Bethlehem, at Cedara it showed the yield of 5.90 tons ha-1 and at Potchefstroom it was 9.95 tons ha-1 and for the average of three sites it was 7.14 tons ha-1. Entry 28 showed grain yield of 5.80 tons ha-1 at Bethlehem, at Cedara it was 5.80 and at Pothefstroom it was 9.35 tons ha-1 and the combined average was 6.98 tons ha-1. These values compared favourably with the commercial standards. The checks entries 58 and 57 had proved to be resistant over locations. The best combiners for Stenocarpella maydis resistance were entries 29 and 52. Stenocarpella maydis ear rot was found to be of polygenic resistance with additive genetic effects.
Thesis (M.Sc. (Crop Science)) --University of Limpopo, 2008
Keywords: Maize; Stenocarpella maydis; 633.50968; Crop improvement